Kondisi Terumbu Karang di Perairan Sisi Timur Pulau Tikus, Bengkulu - Giyanto (OLDI (Oseanologi dan Limnologi di Indonesia), 2026)
Condition of Coral Reefs in the Waters of the East Side of Tikus Island, Bengkulu. Tikus Island is located in the Province of Bengkulu. This small island is about 10 km from the City of Bengkulu. The area is only about 19,800 m2. The waters in the east side of the island was often used as location for the unloading and loading of coal from small ships into large ship (coal transhipment), to be taken to other places. This is because the condition of the port of Baai in Bengkulu is not yet possible for large ships to enter the harbour area. The study to determine the condition of coral reefs in the waters of the east side of Tikus Island was conducted in November 2012. Coral reef data collection was conducted at three stations using Line Intercept Transect (LIT). In addition, the water clarity was also measured using a Secchi disk. The results showed that the water clarity on the east side of Tikus Island was still good for coral growth, with values ranging from 9 to10 m. The percentage of live coral cover was 38.89 ± 5.02%, which was categorized as "fair". This condition was relatively better compared to several other locations that were also located in the Indian Ocean. Supporting data such as the high diversity and density of indicator fish Chaetodontidae as well as the values of heavy metal concentrations in the water columns that are still below the threshold values for marine lives, strengthen the results obtained. Regardless of the presence or absence of negative impacts of coal transhipment occurring in the waters of the east side of Tikus Island, the coral reefs were still in a normal condition.